Manufacturing Value Added and Green Growth in Southern Africa Development Community (Sadc): A Case Study of Malawi - Chalemera, Tamanda Hellen; Ndamsa, Dickson Thomas (EuroEconomica, 2023)
The relationship between manufacturing value-added and green growth is crucial as the manufacturing sector has the potential to drive economic growth but can also have significant environmental consequences. This way, this paper aims to examine the effects of manufacturing value-added on green growth in Malawi. The analysis employs the Autoregressive Distributed Lag (ARDL) model to examine the short and long-term relationship between manufacturing value added and green growth. The ARDL model is estimated using time series data from 1990 to 2019. The results indicate a positive and significant relationship between manufacturing value added and green growth, rejecting the pollution haven hypothesis. This implies that increased manufacturing value added leads to increased green growth. The study also finds that total greenhouse gas emissions impact green growth negatively and significantly. These findings highlight the need to foster green growth by promoting manufacturing value-added activities, encouraging sustainable manufacturing practices, and strengthening environmental regulations and standards.